Surgical outreach and microvascular surgery in developing countries. (June 2018) - Zender, Chad A.; Clancy, Kate; Thuener, Jason E.; Mannion, Kyle
Highlights: Microvascular reconstruction can be incorporated into a surgical outreach program. Patient selection, cost, and infrastructure are challenges to microsurgery in LMIC. Sustainable surgical outreach programs require a strong foundation plus education. Abstract: Due to the discrepancy between surgical demand and resources in Low-Middle Income Countries (LMIC), surgical outreach programs (SOP) have increased in popularity. In these resource-constrained healthcare environments, the resources necessary to perform basic head and neck procedures are often lacking, and offering microvascular reconstruction adds yet another level of complexity. Here we discuss the difficulties and challenges in establishing a SOP abroad and more specifically some of the challenges specific to microvascular reconstruction – including patient selection, burden of cost, lack of infrastructure and equipment, and patient follow up and outcomes. Although challenges certainly exist, we present the feasibility and the benefit for patient care as well as the role it can play in the foundation development of a low-resource region. The goals of the SOP must be well-defined, and incorporating microvascular surgery can be used as an adjunct to enhance the development of many aspects of the LMIC healthcare system. We present a model of care in which the initial focus is centered on providing safe care to these patients undergoing complex procedures, but after the development of a strong foundation, the focus can begin to include program sustainability and education.